2015
DOI: 10.1111/jan.12629
|View full text |Cite
|
Sign up to set email alerts
|

Making reasonable and achievable adjustments: the contributions of learning disability liaison nurses in ‘Getting it right’ for people with learning disabilities receiving general hospitals care

Abstract: Ensuring that reasonable adjustments are made in the general hospital setting promotes person-centred care and equal health outcomes for people with a learning disability. This view accords with 'Getting it right' charter produced by the UK Charity Mencap which argues that healthcare professionals need support, encouragement and guidance to make reasonable adjustments for this group. LDLNs have an important and increasing role to play in advising on and establishing adjustments that are both reasonable and ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 39 publications
(48 reference statements)
0
65
0
Order By: Relevance
“…Whilst there have been examples of nurses with specialist qualifications in ID being appointed in the USA to transition co‐ordinator posts (Betz & Redcay, ) such roles often project based and not sustained. Many UK health services are implementing the role of intellectual disability liaison nurses as a way of operationalizing person‐centred health care in general hospital settings (Castles, Bailey, Gates, & Sooben, ; MacArthur et al., ). This role is recognized as contributing to family support, more effective communication between services and individual clinicians, proactive care and enabling inclusive decision‐making and appropriate levels of autonomy (Brown et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whilst there have been examples of nurses with specialist qualifications in ID being appointed in the USA to transition co‐ordinator posts (Betz & Redcay, ) such roles often project based and not sustained. Many UK health services are implementing the role of intellectual disability liaison nurses as a way of operationalizing person‐centred health care in general hospital settings (Castles, Bailey, Gates, & Sooben, ; MacArthur et al., ). This role is recognized as contributing to family support, more effective communication between services and individual clinicians, proactive care and enabling inclusive decision‐making and appropriate levels of autonomy (Brown et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to highlighting essential components for undergraduate nursing education, this review identifies important professional and ethical issues for inclusion in continuing professional development programmes for all nurses. These include communication and legal issues related to capacity and consent (Sowney & Barr, ), the need for reasonable adjustments to support shared decision‐making and meet specific health needs (MacArthur et al., ; Tuffrey‐Wijne et al., ) and the concept of family centred care (Coyne, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, although there is evidence to suggest that learning disability liaison nursing is valued by stakeholders, 197 and that promoting access and equity is an important part of the role, 198 there appears to have been little formal evaluation of the role 199 and its impact is unclear. Others suggested that the role of a dementia navigator could be non-clinical.…”
Section: Dementia Co-ordinators/support Workersmentioning
confidence: 99%
“…Such posts vary in the way the role is operationalised but generally involve the employment of a nurse with specific intellectual disability knowledge, experience and training within acute hospital settings. Their role is to provide specialist knowledge and expertise and to support the staff working within those settings to provide appropriate care (see, e.g., MacArthur et al., ).…”
Section: Introductionmentioning
confidence: 99%